The role and mechanism of NLRP3 inflammasome-mediated astrocyte activation in dehydrocorydaline against CUMS-induced depression - Fang, Yu; Guo, Hong; Wang, Qiannan; Liu, Congcong; Ge, Shuyi; Yan, Bohua (Frontiers in Pharmacology, 2022)
Background: Depression is a common and potentially life-threatening mental illness, and currently there is a lack of effective treatment. It has been reported that dehydrocorydaline (DHC) can inhibit monoamine transporter uptake in depressed CUMS mice, but more possible mechanisms of action remain to be further studied. Methods: C57BL/6 mice were exposed to chronic unpredictable mild stress (CUMS) for 5 consecutive weeks. The mice were administrated with dehydrocorydaline or fluoxetine (FLU) for 4 consecutive weeks. Behavioral tests including sucrose preference test (SPT), tail suspension test (TST), and forced swimming test (FST) were applied. In parallel, Hematoxylin and eosin (H&E) staining and Nissl staining were used for exploring the effect of DHC on pathological changes in hippocampus. The concentrations of depression-related factors (5-HT and DA) and inflammatory factors (TNF-α, IL-6 and IL-1β) in hippocampus and serum were assessed by ELISA assay. NLRP3 inflammasome pathway-related proteins (NLRP3, IL-18, IL-1 IL-1α and caspase-1) were detected by Western blot. The activation of microglia and astrocytes was subjected to immunofluorescent staining. Additionally, microglia were treated with DHC (100 mg/L) for 24 h following incubated with 100 ng/ml LPS for 12 h. ov-NC or ov-NLRP3 plasmid were transfected into microglia 6 h before LPS induction for exploring the effect of NLRP3 overexpression on DHC inhibited microglia activation. Then, conditioned media of microglia were collected from each group, followed by intervention of astrocytes for 24 h for exploring the effect of NLRP3 overexpression of microglia on astrocytes activation. Results: In vivo the administration of DHC was found to ameliorate depressive-like behaviors and attenuated neuron damage of CUMS mice. DHC can increased neurotransmitter concentration, reduced the pro-inflammatory factors levels, attenuated NLRP3 inflammasome activation, and decreased A1 astrocyte and microglia activation in the hippocampus of CUMS mice. Further in vivo results showed that activated microglia induced activation of A1 astrocytes, but not A2 astrocytes. Conclusion: Taken together, we provided evidence that DHC exhibited anti-depressive effects on CUMS mice possibly via the NLRP3 inflammasome-mediated astrocyte activation.